MOOCs - Haber, Jonathan (MIT Press, 2014)
"Everything you always wanted to know about MOOCs: an account of massive open online courses and what they might mean for the future of higher education."
Keywords: MOOCs (Web-based instruction); Distance education.; Web-based instruction.; Computer-assisted instruction.; Educational technology.; elektronické knihy; electronic books